Quality assurance for the use of computational methods in dosimetry: activities of EURADOS Working Group 6 'Computational Dosimetry'. (26th February 2021) - Rabus, H; Gómez-Ros, J M; Villagrasa, C; Eakins, J; Vrba, T; Blideanu, V; Zankl, M; Tanner, R; Struelens, L; Brkić, H; Domingo, C; Baiocco, G; et al.
Abstract: Working Group (WG) 6 'Computational Dosimetry' of the European Radiation Dosimetry Group promotes good practice in the application of computational methods for radiation dosimetry in radiation protection and the medical use of ionising radiation. Its cross-sectional activities within the association cover a large range of current topics in radiation dosimetry, including more fundamental studies of radiation effects in complex systems. In addition, WG 6 also performs scientific research and development as well as knowledge transfer activities, such as training courses. Monte Carlo techniques, including the use of anthropomorphic and other numerical phantoms based on voxelised geometrical models, play a strong part in the activities pursued in WG 6. However, other aspects and techniques, such as neutron spectra unfolding, have an important role as well. A number of intercomparison exercises have been carried out in the past to provide information on the accuracy with which computational methods are applied and whether best practice is being followed. Within the exercises that are still ongoing, the focus has changed towards assessing the uncertainty that can be achieved with these computational methods. Furthermore, the future strategy of WG 6 also includes an extension of the scope toward experimental benchmark activities and evaluation of cross-sections and algorithms, with the vision of establishing a gold standard for Monte Carlo methods used in medical and radiobiological applications.